Studi Laboratorium Pengaruh Penambahan Fracseal Pada Suhu 80°F, 130°F, 180°F Terhadap Lumpur Pemboran - Yona Tirta Ranti Biu; Eltimeyansi Crisye Randanan; NP, Esterina; Fatma; Nijusiho Manik (Kodepena (Komunitas Dosen Penulis dan Peneliti Indonesia), 2026)
This study aims to evaluate the effect of 3% fracseal addition on the rheological properties and filtration characteristics of drilling mud at temperatures of 80°F, 130°F, and 180°F. The research was conducted experimentally through laboratory testing of plastic viscosity, yield point, gel strength at 10 seconds and 10 minutes, and filtration loss based on API RP 13B-1 standards. The results indicate that standard drilling mud experienced rheological degradation with increasing temperature, characterized by reduced plastic viscosity, excessive gel strength, and increased filtration loss. In contrast, the addition of fracseal improved rheological stability, increased yield point, and reduced filtration loss up to 180°F. These findings suggest that fracseal functions not only as a lost circulation material but also as a rheological stabilizing additive for high-temperature drilling operations.